Malarski a historyczny wizerunek szarży pod Somosierrą na przykładzie szkiców do panoramy „Somosierra” Wojciecha Kossaka - Pawlak, Magdalena J. (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2011)
The charge of Polish light cavalrymen on Spanish batteries in Somosierra passage took place on November 30, 1808. As historic subject it was presented many times on canvases of, among others, Henryk Pillati, Horace Vernet, Piotr Michałowski, January Suchodolski, as well as three generations of Kossak, the family of Polish painters – Juliusz, Wojciech and Jerzy. In 1899 Wojciech Kossak started, in cooperation Michał Wywiórski, preparations for realization of another panorama, the motif of which was to be the above mentioned charge. The whole project was not completed due to political reasons, however, four painting sketches were prepared: La guerrilla (west) – presenting French infantry attacking positions of Spanish troops against the background of a mountain range; Road to Burgos (north) with Napoleon on a bridge and Polish light cavalrymen; Charge on Spanish batteries (east) presenting the real charge between the first and the second Spanish batteries; The road to Madrid is opened (south), where landscape is dominant and battle accent constitute silhouettes of running away Spanish soldiers and partisans. As opposed to earlier painting evocations, the sketches for the panorama were preceded with solid historic and field studies in Spain, as well as consultations with gen. Aleksander Puzyrewski, a recognized author of historic works about Napoleonic wars. Landscape backgrounds made by M. Wywiórski were conformable with the local topography, whereas Wojciech Kossak, as one of only a few painters, who presented the fighting soldiers in battle uniforms. Therefore, the above sketches are the most accurate attempt to reconstruct the historic image of the charge. In 1899 Wojciech Kossak started, in cooperation Michał Wywiórski, preparations for realization of another panorama, the motif of which was to be the above mentioned charge. The whole project was not completed due to political reasons, however, four painting sketches were prepared: La guerrilla (west) – presenting French infantry attacking positions of Spanish troops against the background of a mountain range; Road to Burgos (north) with Napoleon on a bridge and Polish light cavalrymen; Charge on Spanish batteries (east) presenting the real charge between the first and the second Spanish batteries; The road to Madrid is opened (south), where landscape is dominant and battle accent constitute silhouettes of running away Spanish soldiers and partisans. As opposed to earlier painting evocations, the sketches for the panorama were preceded with solid historic and field studies in Spain, as well as consultations with gen. Aleksander Puzyrewski, a recognized author of historic works about Napoleonic wars. Landscape backgrounds made by M. Wywiórski were conformable with the local topography, whereas Wojciech Kossak, as one of only a few painters, who presented the fighting soldiers in battle uniforms. Therefore, the above sketches are the most accurate attempt to reconstruct the historic image of the charge.